Origami Game for Improving Fine Motor Skills for Children 4-5 Years Old in Gang Buaya Village in Salatiga - Ester Steffi Cllaudia; Ajeng Ayu Widiastuti; Mozes Kurniawan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of this study was to improve the fine motor skills of 4-5-year-old children through origami games in Kampung Gang Buaya Salatiga. Attractive origami paper folding activities can motivate children to improve their fine motor skills. This type of research is Participatory Action Research (PAR) conducted through 2 cycles. The research subjects were SI 5 girls and 4 boys. Data collection techniques use interviews and documentation. The research object is children's fine motor skills through origami paper games. Data Analysis Techniques using Quantitative Descriptive. Branch stitching can be seen from the average fine motor skills of children with origami paper applications with the criteria of Developing According to Hope that is 76%. The results of this study indicate an increase in children's fine motor skills through playing origami paper in the village of Gang Buaya Salatiga, which is seen from the children's fine motor skills in the pre-action stage, which is an average of 33.3% to 65.38% in cycle I actions, then increased to 79.62% in the transition period II.